IMPLEMENTATION OF PATEN (SUB-DISTRICT INTEGRATED ADMINISTRATIVE SERVICES) POLICY THROUGH E-KTP PROGRAM IN KRIAN SUB-DISTRICT - Budi, Ari Setia; Rodiyah, Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to explore the execution of the Integrated Administrative Services at the Subdistrict level (PATEN) through the e-KTP program in Krian District, Sidoarjo Regency. The research background is rooted in the necessity to enhance the effectiveness of public services along with the demands for bureaucratic reform in population administration. Method: The methodology employed is qualitative descriptive, utilizing observation, interviews, and documentation techniques. The analysis is based on the implementation theory by George C. Edward III, which includes four primary variables: communication, resources, disposition, and bureaucratic structure. Results: The study's findings reveal that regarding communication, the policy implementation is effective due to a clear and coordinated top-down communication pattern. In terms of resources, the availability of human resources, equipment, and funding is considerably supportive, although there is still a need for improvements in both quantity and quality, particularly during peak hours. From the perspective of disposition, the officers exhibit strong commitment and understanding of their duties and actively participate in technical training. However, a significant challenge is identified in the bureaucratic structure, where the authority for e-KTP printing remains centralized in the Ministry of Home Affairs, leading to delays and uncertainties in service. Novelty: The innovation of this research lies in its analysis of the implementation of PATEN in the context of e-KTP services and the pressing need for the decentralization of authority, enhancement of human resource capacity, and improvement of service infrastructure as part of the public service transformation at the subdistrict level.